Dental amalgam exposure can elevate urinary mercury concentrations in children. (1st February 2016) - Baek, Hye‐Jin; Kim, Eun‐Kyong; Lee, Sang Gyu; Jeong, Seong‐Hwa; Sakong, Jun; Merchant, Anwar T.; Im, Sang‐Uk; Song, Keun‐Bae; Choi, Youn‐Hee
Abstract : Objectives: Owing to its cost‐effectiveness and operative convenience, dental amalgam remains in use as a restorative material for tooth caries in children in many countries. The aim of this study was to evaluate the relationship between dental amalgam exposure and urinary mercury (U‐Hg) concentrations in children. Methods: In this longitudinal study, 463, 367 and 348 children, 8–11 years of age, were evaluated at baseline, and at the first and second follow‐up visits, respectively. The interval between each survey was 6 months. For the oral examination and urine sample, the amalgam‐filled tooth surface (TS), and U‐Hg and creatinine concentrations of participants were determined, and the cumulative amalgam‐filled TS and cumulative creatinine‐adjusted U‐Hg were calculated. To assess potential covariates, socio‐demographic factors, oral health behaviour and dietary factors were surveyed by questionnaire. Data were analysed by the t ‐test, correlation analysis and mixed‐model analysis. The statistical analyses were performed using SPSS 18.0. Results: Children with more than one amalgam‐filled TS exhibited significantly higher creatinine‐adjusted U‐Hg concentrations than those without, in all three survey periods ( P < 0.001). The results for the current and cumulative amalgam‐filled TS significantly correlated with those for the current and cumulative creatinine‐adjusted U‐Hg concentration, respectively, in all surveys ( P < 0.001). In the repeated‐measures mixed model analysis, current and cumulative amalgam‐filled TS was significantly related to current and cumulative creatinine‐adjusted U‐Hg concentration, respectively ( P < 0.001). Conclusions: Amalgam‐filled TS was significantly correlated with U‐Hg concentrations in children. Therefore, dental amalgam exposure can affect the systemic mercury concentration in children.